2017
DOI: 10.1111/cas.13298
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ITGA3 by the anti‐tumor miR‐199 family inhibits cancer cell migration and invasion in head and neck cancer

Abstract: For patients with head and neck squamous cell carcinoma (HNSCC), survival rates have not improved due to local recurrence and distant metastasis. Current targeted molecular therapies do not substantially benefit HNSCC patients. Therefore, it is necessary to use advanced genomic approaches to elucidate the molecular mechanisms underlying the aggressiveness of HNSCC cells. Analysis of our microRNA (miRNA) expression signature by RNA sequencing showed that the miR‐199 family (miR‐199a‐5p, miR‐199a‐3p, miR‐199b‐5p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
112
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 117 publications
(116 citation statements)
references
References 53 publications
(88 reference statements)
2
112
1
1
Order By: Relevance
“…Previous reports showed that overexpression of SERPINH1 promotes procollagen production, resulting in the development of the epithelial mesenchymal transition . Recent studies suggested that aberrantly expressed ECM genes and their receptors enhanced cancer cell aggressiveness . Elucidation of genes modulated by SERPINH1 might provide novel therapeutic approaches in RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that overexpression of SERPINH1 promotes procollagen production, resulting in the development of the epithelial mesenchymal transition . Recent studies suggested that aberrantly expressed ECM genes and their receptors enhanced cancer cell aggressiveness . Elucidation of genes modulated by SERPINH1 might provide novel therapeutic approaches in RCC.…”
Section: Discussionmentioning
confidence: 99%
“…After a 48‐hour incubation period, miRNAs were isolated by immunoprecipitation using a microRNA Isolation Kit for Human Ago2 (Wako, Osaka, Japan). We then assessed the expression of Ago2‐conjugated miRNAs by qRT‐PCR, as described in previous studies …”
Section: Methodsmentioning
confidence: 99%
“…The clinical significance of miRNAs and their target genes in LUSQ was investigated with TCGA database (https://tcga-data.nci.nih.gov/tcga/). The gene expression and clinical data were retrieved from cBioPortal (http://www.cbioportal.org/) and OncoLnc (http://www.oncolnc.org) (data downloaded on April 28, 2018) …”
Section: Methodsmentioning
confidence: 99%
“…In the search miRNA database (miRBase: http://www.mirbase.org/), the expression of miR‐199a/b‐3p annotated as passenger strands is higher than that of miR‐199a/b‐5p . Our previous study also showed that the expression level of miR‐199a/b‐3p in head and neck cancer was more abundant than miR‐199a/b‐5p . These facts might indicate characteristics of the miR‐199 family, suggesting that the passenger strand could exert more function in the cell in the miR‐199 family.…”
Section: Resultsmentioning
confidence: 86%
“…The miR‐199 family members reportedly act as tumor suppressors in several cancers. Recently, we showed that all members of the miR‐199 family acted as antitumor miRNAs through their targeting of integrin‐mediated oncogenic signaling in head and neck squamous cell carcinoma . In PCa, downregulation of miR‐199a‐5p and miR‐199b‐5p induced HIF‐1α expression, and these events enhanced PCa development .…”
Section: Discussionmentioning
confidence: 99%